Aplikasi Susu Skim Pada Pembuatan Kefir Soya - irma, Adek (Universitas Muhammadiyah Sumatera Utara, 2023)
Soy milk is a nutrient-wealthy drink. One manner to enhance the great of soy milk through processing it right into a probiotic drink is kefir soy milk. The purpose of this study to decide the impact of additional awareness of skim milk on the best of kefir soy milk is visible from the physical properties of chemistry, microbiology and organoleptik. This research was conducted by Completely Randomized Design (CRD) method in two stages: Determination of concentration of skim milk is 2%, 4%, 6% and 8%. Then followed by the addition of kefir stater concentration that is 2%, 4%, 6% and 8%. The prameters is total microbes, pH, alcohol content, TSS and organoleptic flavor. The addition of skim milk had a totally massive impact on p 0.01 on total microbial, pH, alcohol content material, flavor and TSS. The attention of kefir staterum has very extensive effect on p 0,01 to total microbial, pH, TSS, flavor and exclusive no longer significant with alcohol content material. The great effects were received on the S3K4 treatment. At alcohol content of zero.360% in line with the chemical composition of kefir.